2019
DOI: 10.1186/s12884-019-2332-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of disrespect and abuse during facility based child birth and associated factors, Jimma University Medical Center, Southwest Ethiopia

Abstract: Background In countries where the proportion of births attended by skilled providers is low, maternal mortality is high. According to the 2016 EDHS report, the proportion of births attended by skilled providers was only 26% and the maternal mortality ratio was 412 per 100,000 live-births. Disrespectful and abusive behavior of health workers and other facility staff experienced by women during facility-based childbirth is important, but the little-understood barrier of institutional delivery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
69
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(101 citation statements)
references
References 16 publications
14
69
11
1
Order By: Relevance
“…However, our study demonstrates that 40% of participating women felt ignored/abandoned and 12.9% of women reported healthcare providers were not present when the baby was born. This nding is in line with a study conducted in the southwest of Ethiopia (31). Furthermore, women should be able to have a birth companion of their choice.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…However, our study demonstrates that 40% of participating women felt ignored/abandoned and 12.9% of women reported healthcare providers were not present when the baby was born. This nding is in line with a study conducted in the southwest of Ethiopia (31). Furthermore, women should be able to have a birth companion of their choice.…”
Section: Discussionsupporting
confidence: 88%
“…Unfortunately, in this study, 29% of women reported non-digni ed care. Previous studies have documented similar result elsewhere in Ethiopia (21,23,31,33). Non-digni ed care and insults may drive women away from healthcare facilities towards less trained providers who treat them with dignity and respect (40).…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations